Clostridium difficile Infection and Colorectal Surgeries: A Narrative Review - Abbas Abdollahi; Ala Orafaie; Fatemeh Shahabi; Majid Ansari (Reviews in Clinical Medicine)
Clostridium difficile infection (CDI) is a significant health-related infection rarely seen in colorectal patients after surgery. However, over the past two decades, there has been an increase in the incidence and severity of CDI. In addition, the healthcare system is impacted significantly by the morbidity, mortality, and costs associated with CDI. While antibiotic use was initially thought to be the only cause, CDI has now been associated with hospitalization and residence in long-term care facilities. The risk of developing CDI is higher for patients who undergo gastrointestinal procedures, including colectomy. Hence, targeting preventive measures and reducing the burden associated with CDI can be achieved by identifying colorectal surgery patients at high risk for this increasingly prevalent disease. In the present article, we aim to review the current evidence of pre- and postoperative CDI in patients with underlying colorectal surgeries due to benign or malignant conditions, pointing to risk factors for infection, clinical impact, and outcomes.